LUBLIN AT WORK OF THE PEDAGOGUE - RESOURCES OF THE CITY IN EDUCATIONAL ACTIVITIES. PART 1. MUSEUMS - Anna Bieganowska-Skóra (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
This text analyzes the educational offer of Lublin museums. An attempt was made to answer the question whether, when planning educational activities, the employees of the centers take into account the needs of the young generation and the recommendations of didactics, or the effects of their work are attractive to children and youth. The description was supplemented with lists of proposals for classes offered to pupils of kindergartens and schools by institutions included in the Lublin Museum in Lublin and the Museum of the Lublin Village, the Majdanek Museum and the Regional Onion Museum.